İŞ HUKUKU BOYUTUYLA TÜRKİYE'DE PSİKOLOJİK TACİZ (MOBBING) VE DÜNYADAN ÖRNEKLER - (:unkn) unknown (My University, 2014)
Bu makalede, günümüzde çalışma hayatının önemli bir sorunu olarak karşımıza çıkan, işçinin gerek kişilik haklarına ve sağlığına gerekse kariyerine ağır şekilde zarar veren psikolojik taciz (mobbing) süreci incelenmektedir. Bu kapsamda, psikolojik taciz kavramı, tanımı, unsurları, ortaya çıkışı, sonuçları, konuya ilişkin mevcut kanuni düzenlemeler, Yargıtayın ilgili kararları da dikkate alınmak suretiyle açıklığa kavuşturulmaktadır. Yine uluslararası alanda sergilenen bakış açısına örnek teşkil etmesi amacıyla, bazı ülkelerin psikolojik tacize ilişkin yasal düzenlemeleri de ele alınmaktadır.

The aim of this article is to review the psycological harassment issue that heavily damages the worker s personal rights, health and professional career, and which also is one of the important problems that we encounter in the professional life of today. Within this context, the concept of psychological harassment, definition, factors, occurance, results, related legal regulations are being clarified while also taking decisions of the Turkish Supreme Court into consideration. In addition to these, in order to provide examples for the global perspective, legal regulations of some countries regarding psychological harassment are also reviewed.
Pyschological Harassment in Turkish Labor Law and Global App lications
Keywords: İş; Uluslararası İlişkiler; Hukuk